Una mirada reflexiva al modelo escuela nueva de la institución educativa Guaimaral (Sede Altomira) (2019)
Faced with the purpose of conducting a thoughtful analysis on the contribution of the new school model applied in the Guaimaral educational institution (Altomira headquarters), reference sources such as: Colbert (1999), Colbert (2006), MEN (2010), Jaimes (2018), Gómez (1995), Santos (2011), among others. Thus, the methodology of investigation used was qualitative; with an ethnographic approach and using the case study strategy. The informal interview was used for information collection. The results indicate that the application of the new school model can promote active and thoughtful learning of students attending the Guaimaral Educational Institution, Altomira headquarters. It is concluded that if this model complied with all theoretical and practical guidelines it would have been a model of the highest quality, which has in fact been successful in other institutions, not only in Colombia, but also in countries, such as Mexico, Uruguay, Salvador, among others.